2022
DOI: 10.2196/43757
|View full text |Cite
|
Sign up to set email alerts
|

Model for Predicting In-Hospital Mortality of Physical Trauma Patients Using Artificial Intelligence Techniques: Nationwide Population-Based Study in Korea

Abstract: Background Physical trauma–related mortality places a heavy burden on society. Estimating the mortality risk in physical trauma patients is crucial to enhance treatment efficiency and reduce this burden. The most popular and accurate model is the Injury Severity Score (ISS), which is based on the Abbreviated Injury Scale (AIS), an anatomical injury severity scoring system. However, the AIS requires specialists to code the injury scale by reviewing a patient's medical record; therefore, applying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Our previous study [ 5 ] revealed that blood pressure, heart rate, body temperature, and other vital signs weakened the previous AI model’s performance, whereas incorporating vital signs strengthened our present AI model. This observation implies that ED and in-hospital mortality patients exhibit differing data distributions.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Our previous study [ 5 ] revealed that blood pressure, heart rate, body temperature, and other vital signs weakened the previous AI model’s performance, whereas incorporating vital signs strengthened our present AI model. This observation implies that ED and in-hospital mortality patients exhibit differing data distributions.…”
Section: Resultsmentioning
confidence: 50%
“…Thus, patients with multiple injuries were excluded from exclusive SRR calculations [ 20 ]. We used the survival probability determined from our previous study [ 5 ] because other studies [ 20 , 21 ] did not use ED mortality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a strategy may greatly help clinicians in facilitating patient risk assessment and triaging and optimize resource use. Elsewhere, machine-learning-based models predicted the need for urgent neurosurgery [44] or trauma mortality [45]. The potential clinical benefits of such models as decision-making and triage tools deserve further assessment in the prehospital environment.…”
Section: Discussionmentioning
confidence: 99%